Surveillance Data for Eight Consecutive Influenza Seasons in Sicily, Italy - Tramuto, Fabio (Am J Trop Med Hyg, 2019)
Influenza A and B outbreaks occur each year with different activity and molecular patterns. To date, knowledge of seasonal epidemiology remains a prerequisite not only to put in place the most effective immunization strategy against influenza but also to identify population groups at higher risk of developing serious complications. A retrospective analysis of influenza surveillance data from 2010 to 2018 aimed to explore the epidemiology of influenza in Sicily, at the primary care and hospital level. Overall, 6,740 patients with acute respiratory infection were tested, of which 3,032 (45.0%) were positive for influenza. The relative proportion of type A and B viruses markedly varied across seasons. Type A similarly spreads among children and adults, whereas type B was more commonly identified among pediatric population aged 5–9 years. The median age of confirmed influenza cases differed by health-care setting, increasing according to disease severity (range: 8–54 years). Among influenza-confirmed cases, more than 80% of hospitalized patients had an underlying medical condition. Cardiovascular disease, lung disease, diabetes, and obesity were some of the most frequent. Overall, patients admitted to an intensive care unit were more likely to have multiple comorbidities and being infected with influenza infection strongly increased the risk of severe clinical outcomes. Understanding of the epidemiology of influenza and the molecular features of circulating viruses is of paramount importance to optimize prevention and control strategies. Knowledge of predictors for the occurrence of severe forms of the disease may help to address adequate preventive measures to high-risk population groups.